Dorsomedial prefrontal cortex activity predicts the accuracy in estimating others' preferences - Kang, Pyungwon; Lee, Jongbin; Sul, Sunhae; Kim, Hackjin (Frontiers in Human Neuroscience, 2013)
The ability to accurately estimate another person’s preferences is crucial for successful social life. In daily interactions, we often do this on the basis of minimal information. The aims of the present study were a) to examine whether people can accurately judge about others based only on a brief exposure to their appearances, and b) to reveal the underlying neural mechanisms using fMRI. Participants were asked to make guesses about unfamiliar target individuals’ preferences for various items after looking at their faces for 3 seconds. Behavioral results showed that participants estimated others' preferences above chance level. Functional magnetic resonance imaging (fMRI) data revealed that higher accuracy in preference estimation was associated with greater activity in dorsomedial prefrontal cortex (DMPFC) while participants were guessing targets’ preferences relative to thinking about their own preferences. These findings suggest that accurate estimation of others' preferences may require increased activity in DMPFC. Functional connectivity analysis revealed that higher accuracy in preference estimation was related to increased functional connectivity between DMPFC and brain regions that are known to be involved in theory of mind (ToM) processing, such as temporoparietal junction (TPJ) and posterior cingulate cortex (PCC)/precuneus during correct vs. incorrect guessing trials. These findings imply that DMPFC may be a core part in estimating preferences of others and that higher accuracy may require stronger communication between DMPFC and a network of neural structures including TPJ and PCC/precuneus, which are now widely known to be involved in taking another person 's perspective during mentalizing.